Case Report: Placental Maternal Vascular Malperfusion Affecting Late Fetal Development and Multiorgan Infection Caused by SARS-CoV-2 in Patient With PAI-1 4G/5G Polymorphism - JAK, Behling; Zanirati, Gabriele; Rodrigues, Felipe V. F.; Grahl, Matheus; Krimberg, Felipe; Pinzetta, Giulia; Borém, Larissa; Savi, Daniela; Machado, Denise Cantarelli; Da Costa, Jaderson Costa; Marinowic, Daniel Rodrigo (Frontiers in Medicine, 2021)
Background: Pregnant women are susceptible to the novel coronavirus (SARS-CoV-2), and the consequences for the fetus are still uncertain. Here, we present a case of a pregnant woman with subclinical hypothyroidism and a plasminogen activator inhibitor type 1 (PAI-1) 4G/5G polymorphism who was infected with SARS-CoV-2 at the end of the third trimester of pregnancy, with unexpected evolution of death of the newborn 4 days postpartum. Methods: Nested PCR was performed to detect the virus, followed by ssDNA sequencing. Results: Transplacental transmission of SARS-CoV-2 can cause placental inflammation, ischemia, and neonatal viremia, with complications such as preterm labor and damage to the placental barrier in patients with PAI-1 4G/5G polymorphism. Conclusion: We showed a newborn with several damages potentially caused due to the PAI-1 polymorphisms carried by the mother infected with SARS-CoV-2 during pregnancy.